2016
DOI: 10.1038/srep28465
|View full text |Cite
|
Sign up to set email alerts
|

pH-Selective Cytotoxicity of pHLIP-Antimicrobial Peptide Conjugates

Abstract: Positively charged antimicrobial peptides have become promising agents for the treatment of cancer by inducing apoptosis though their preferential binding and disruption of negatively charged membranes, such as the mitochondrial membrane. (KLAKLAK)2 is such a peptide but due to its polarity, it cannot cross the cellular membrane and therefore relies on the use of a delivery agent. For targeted delivery, previous studies have relied on cell penetrating peptides, nanoparticles or specific biomarkers. Herein, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 38 publications
4
65
0
Order By: Relevance
“…However, one of the biggest therapeutic and biotechnical developments of these antimicrobial molecules has been to provide guidance to the design of novel compounds with pH dependent activity against: bacteria [303,304], fungi [46,305,306] and cancer cells [307,308] as well as applications involving drug [309,310] and gene delivery [311,312]. As a specific example, most AMPs designed to target the low pH of tumor tissue are cationic and cytotoxicity to healthy tissue at physiological pH has often been an issue for these peptides [98,279,280]. To address this issue, a peptide based on magainin 2 from X. laevis was designed to possess a negative charge at neutral pH that switched to a strong positive charge at low pH for cancer targeting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one of the biggest therapeutic and biotechnical developments of these antimicrobial molecules has been to provide guidance to the design of novel compounds with pH dependent activity against: bacteria [303,304], fungi [46,305,306] and cancer cells [307,308] as well as applications involving drug [309,310] and gene delivery [311,312]. As a specific example, most AMPs designed to target the low pH of tumor tissue are cationic and cytotoxicity to healthy tissue at physiological pH has often been an issue for these peptides [98,279,280]. To address this issue, a peptide based on magainin 2 from X. laevis was designed to possess a negative charge at neutral pH that switched to a strong positive charge at low pH for cancer targeting.…”
Section: Discussionmentioning
confidence: 99%
“…As major examples, lactoferrin and its derivatives have been extensively investigated as potential drugs for the treatment of common viral infections including the common cold, influenza, viral gastroenteritis and herpes [275] whilst the inhibitory effects of these proteins and peptides against the proliferation of multiple cancers, has suggested a potential role in cancer prevention [276]. It is well established that many AMPs and antimicrobial proteins have anticancer activity that generally appears to involve mechanisms of membranolysis that are similar to those used by these molecules in their action against microbes [277,278], which in some cases shows pH dependence [98], as recently described [279,280]. Advanced clinical trials have shown that the administration of lactoferrin has no significant side effects and that the protein has efficacy in treating iron deficiency anemia in pregnant women [281], sepsis in premature neonates, which is a common and severe complication in new-born infants [282] and infections due to Helicobacter pylori , which is causally associated with gastritis and peptic ulcer diseases [283].…”
Section: Potential Applications Of Ph Dependent Antimicrobial Peptmentioning
confidence: 99%
“…714 We recently showed that pHLIP provides localized delivery of monomethyl auristatin E (MMAE) to cancer cells. 12 This previous study shows that pHLIP-mediated translocation of MMAE inhibits the proliferation of cancer cells in a pH-selective and concentration-dependent fashion and that it offers clear advantages over treatment with free MMAE.…”
Section: Introductionmentioning
confidence: 99%
“…Within pHLIP there are multiple D/E residues which could sense the pH change,t he particular role played by eacho ft hem in the protonation-driven insertion process is not clear.T he precise location of the TM helix within the pHLIP sequence is also unknown. [11][12][13][14][15][16][17][18][19][20] To extend the biomedical applications of pHLIP to broader systems with higher efficiency,a ppropriate tuning of its primary sequence is necessary, [21,22] and to do so requires an in-depth and detailed understanding of its pH-regulated membrane insertion process,which is currently not available.Them acroscopic, apparent pH 50 ,d efined as the pH at which 50 %o ft he pHLIP molecules are inserted (also referred to as pK or pK a of insertion by others), has been estimated to be about 6.1-6.2 by following fluorescence changes of Wresidues at positions 9and 15. Residue-specific pK a values of D31, D33, D25, and D14 were determined to be 6.5, 6.3, 6.1, and 5.8, respectively,a nd define the sequence of protonations which lead to insertion.…”
mentioning
confidence: 99%